First evidence of cytotoxic effects of human protozoan parasites on zebra mussel (Dreissena polymorpha) haemocytes. Issue 3 (18th December 2018) - Le Guernic, Antoine; Geffard, Alain; Rioult, Damien; Bonnard, Isabelle; Le Foll, Frank; Palos Ladeiro, Mélissa
Summary: The interaction between human protozoan parasites and the immune cells of bivalves, that can accumulate them, is poorly described. The purpose of this study is to consider the mechanisms of action of some of these protozoa on zebra mussel haemocytes, by evaluating their cytotoxic potential. Haemocytes were exposed to Toxoplasma gondii, Giardia duodenalis or Cryptosporidium parvum (oo)cysts. The results showed a cytotoxic potency of the two largest protozoa on haemocytes and suggested the formation of haemocyte aggregates. Thus, this study reveals the first signs of a haemocyte:protozoan interaction.